Chitosan & Conductive PANI/Chitosan Composite Nanofibers - Evaluation of Antibacterial Properties - Moutsatsou, Panagiota; Coopman, Karen; Georgiadou, Stella (Current Nanomaterials, 2019)
Background: Within the healthcare industry, including the care of chronic wounds, the challenge of antimicrobial resistance continues to grow. As such, there is a need to develop new treatments that can reduce the bioburden in wounds. Objective: The present study is focused on the development of polyaniline (PANI) / chitosan (CH) nanofibrous electrospun membranes and evaluates their antibacterial properties. Methods: To this end, experimental design was used to determine the electrospinning windows of both pure chitosan and PANI/CH blends of different ratios (1:3, 3:5, 1:1). The effect of key environmental and process parameters (relative humidity and applied voltage) was determined, as well as the effect of the PANI/CH ratio in the blend and the molecular interactions between PANI and chitosan that led to jet stability. Results: The nanofibrous mats were evaluated regarding their morphology and antibacterial effect against model gram positive and gram negative bacterial strains, namely B. subtilis and E. coli. High PANI content mats show increased bactericidal activity against both bacterial strains. Conclusion: The blend fibre membranes combine the materials’ respective properties, namely electrical conductivity, biocompatibility and antibacterial activity. This study suggests that electrospun PANI/CH membranes are promising candidates for healthcare applications, such as wound dressings.
Keywords: chitosan